The Relationship Between Nutritional Status and Early Menarche: A Narrative Review - Nafiisah Zana Dzakiyah (Yayasan Literasi Sains Indonesia, 2026)
This narrative review examines the relationship between nutritional status and the timing of menarche in adolescent girls, with a particular focus on early menarche. It explores how nutritional status influences pubertal onset and the associated health risks amid the increasing global prevalence of childhood overweight. A literature search of studies published between 2015 and 2025 was conducted using PubMed, Google Scholar, and ScienceDirect, resulting in five eligible cross-sectional studies from Brazil and Indonesia. The findings consistently indicate that higher body mass index (BMI) is significantly associated with menarche before age 12, potentially through hormonal mechanisms involving leptin and activation of the hypothalamic–pituitary–gonadal axis. Early menarche is associated with greater risks of metabolic, reproductive, and psychosocial health problems. Public health interventions should promote balanced nutrition, regular physical activity, and routine growth monitoring to support healthy pubertal development. Further longitudinal studies are needed to establish causal relationships and identify additional factors influencing the timing of menarche.